2015
DOI: 10.1186/s12967-015-0433-0
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic properties of a vector carrying the HSV thymidine kinase and GM-CSF genes and delivered as a complex with a cationic copolymer

Abstract: Background: Gene-directed enzyme prodrug therapy (GDEPT) represents a technology to improve drug selectivity for cancer cells. It consists of delivery into tumor cells of a suicide gene responsible for in situ conversion of a prodrug into cytotoxic metabolites. Major limitations of GDEPT that hinder its clinical application include inefficient delivery into cancer cells and poor prodrug activation by suicide enzymes. We tried to overcome these constraints through a combination of suicide gene therapy with immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 102 publications
1
18
0
1
Order By: Relevance
“…MPO was fabricated with the adsorption of cations and anions which could significantly decreased the cytotoxicity induced by cations of PEI. The safety of modified PEI was confirmed in a variety of animal experiments [38,39]. The two points above made MPO safety and low toxicity for future clinic application.…”
Section: Discussionmentioning
confidence: 81%
“…MPO was fabricated with the adsorption of cations and anions which could significantly decreased the cytotoxicity induced by cations of PEI. The safety of modified PEI was confirmed in a variety of animal experiments [38,39]. The two points above made MPO safety and low toxicity for future clinic application.…”
Section: Discussionmentioning
confidence: 81%
“…We previously [ 5 ] showed that the linking of histone H2A with HIV TAT-peptide enhanced the transfection efficiency of histone, likely due to the high positive charge of the peptide, allowing efficient binding to negatively charged cell membranes and subsequent internalization of the complexes. TAT-peptide was also used to enhance the efficiency of polyethyleneimine (PEI)-polyethylene glycol (PEG) copolymer and successfully applied for DNA delivery during suicide gene therapy in a murine tumor model [ 29 ]. Ligands of cell surface receptors that induce their internalization are also frequently used as non-viral carriers.…”
Section: Discussionmentioning
confidence: 99%
“…The expressed cytokine has shown all biological activities of recombinant human IL-12, such as the stimulation of proliferation of the activated natural killer (NK) and T-cells, induction of the interferon-gamma (IFN-γ) secretion by NK and T-cells, and enhancement of lymphokine-activated killer (LAK) activity [89]. There are other constructs simultaneously encoding several cytokines [90,91]. For example, co-expression of IL-2 and tumor necrosis factor (TNF-α), linked by IRES, in an oncolytic adenovirus genome, has allowed increases in the number of CD4 + and CD8 + tumor-infiltrating lymphocytes, as well as T-helper 1 (Th1) and CD86 + dendritic cells (DCs) in vivo [90,92].…”
Section: Multicistronic Vectors For Cancer Therapymentioning
confidence: 99%